EULAR points to consider for conducting clinical trials in systemic lupus erythematosus. Issue 4 (3rd April 2008) - Gordon, C; Bertsias, G; Ioannidis, J P A; Boletis, J; Bombardieri, S; Cervera, R; Dostál, C; Font, J; Gilboe, I-M; Houssiau, F; Huizinga, T W J; Isenberg, D; et al.
Abstract : Objective: Systemic lupus erythematosus (SLE) is a complex multi-organ disease, characterised by relapses and remissions. Designing a high-quality randomised controlled trial poses many challenges. We have developed evidenced-based recommendations for points to consider in conducting clinical trials in patients with SLE. Methods: The EULAR Task Force on SLE comprised 19 specialists and a clinical epidemiologist. Initially, the evidence for clinical trial end-points in SLE was evaluated and this has been reported separately. A consensus approach was developed by the SLE Task Force in formulating recommendations for points to consider when conducting clinical trials in SLE. Results: The literature review revealed that most outcome measures used in phase 2/3 trials in SLE have not actually been validated in clinical trials, although other forms of validation have been undertaken. The final recommendations for points to consider for conducting clinical trials in SLE address the following areas: study design, eligibility criteria, outcome measures including adverse events, concomitant therapies for SLE and its complications. Conclusions: Recommendations for points to consider when conducting clinical trials in SLE were developed using an evidence-based approach followed by expert consensus. The recommendations should be disseminated, implemented and then reviewed in detail and revised using an evidence-based approach in about 5 years, by which time there will be further evidence to consider from current clinical trials.